Clinical Dengue among Travelers and Non-Travelers in Greater Barishal (The Planet, 2021)
Dengue fever is a mosquito borne disease caused by an arbovirus and expansion of dengue fever to new countries and, from urban to rural settings constitutes an important health problem in the world including Bangladesh. The incidence of dengue infection in Barishal division with and without travel history to known endemic area has been investigated in the current cross sectional study in Sher-e-Bangla medical College Hospital in August, 2019in sample size of 212 admitted patents of whom 138 (65.1%) were male, 74 (34.9 %) were female,116 (54.7%) of patients traveled to a known endemic zone, 96 (45.3%) did not; 206 (97.2%) were NS1 positive, 4 (1.9%) were IgM positive, 2 (0.9%) were IgM positive and IgG positive; Of travelling 116 patients, 92(79.3%) were male, 24(20.7%) were female and among the non-travelling96 patients 46(47.9%) were male, 50(52.1%) were female. This study concluded that Dengue is spreading to previously non-endemic zones like greater Barishal and travelers hold the major share of disease burden. Male preponderance in traveling to endemic zone was statistically significant (p=0.001).
Keywords: Dengue; Aedes aegypti; Serotype; NS1 antigen; Enedemic